2019
DOI: 10.1177/0361198119827936
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Interstate Work Zone Mobility using Probe Vehicle Data and Machine Learning Techniques

Abstract: According to the Federal Highway Administration (FHWA), US work zones on freeways account for nearly 24% of nonrecurring freeway delays and 10% of overall congestion. Historically, there have been limited scalable datasets to investigate the specific causes of congestion due to work zones or to improve work zone planning processes to characterize the impact of work zone congestion. In recent years, third-party data vendors have provided scalable speed data from Global Positioning System (GPS) devices and cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…When there are people or heavy equipment in the work area, drivers often adhere to the speed limit in the work area [29]. Kamyab, M. [30] used machine learning to predict the influencing factors of future work areas and found that long-term speed changes are important factors in predicting the impact of work areas on traffic. Pesti, G. [10] developed a method for evaluating the impact of road construction work areas, (a) predicting the network level impact of road construction projects, (b) identifying key sections and corridors with the most severe expected construction impact, and (c) comparing alternative construction plans and schedules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When there are people or heavy equipment in the work area, drivers often adhere to the speed limit in the work area [29]. Kamyab, M. [30] used machine learning to predict the influencing factors of future work areas and found that long-term speed changes are important factors in predicting the impact of work areas on traffic. Pesti, G. [10] developed a method for evaluating the impact of road construction work areas, (a) predicting the network level impact of road construction projects, (b) identifying key sections and corridors with the most severe expected construction impact, and (c) comparing alternative construction plans and schedules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These data were verified by numerous sources including the I-95 Corridor coalition ( 21 ). Since then, these data have been used in different areas of work zone traffic mobility including impact measurement ( 22 – 24 ), congestion and bottle neck evaluation ( 2527 ), and traffic mobility prediction ( 11 , 24 , 28 ).…”
Section: Probe Vehicle Datamentioning
confidence: 99%
“…In both studies, hourly traffic volume was used as the critical input to train the predictive models. In the absence of hourly traffic volume, a classification modeling approach was introduced, in an earlier attempt, to predict speed ranges for each highway segment during lane closure events ( 24 ). Distributions of historical traffic speeds were used to provide a mobility baseline for random forest and XGBoost classification algorithms ( 24 ).…”
Section: Probe Vehicle Datamentioning
confidence: 99%
See 1 more Smart Citation
“…These applications analyze and fuse data from multiple sources to extract useful information or predictions that would otherwise be difficult to elicit. For example, traffic flow and incidents can be used to model and even predict future conditions (13)(14)(15). Similarly, safety research has used machine learning techniques to uncover hidden outcomes by fusing multiple data sources, such as land use and demographics (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%